2021
DOI: 10.7717/peerj.10633
|View full text |Cite
|
Sign up to set email alerts
|

Gene signatures with predictive and prognostic survival values in human osteosarcoma

Abstract: Osteosarcoma is a common malignancy seen mainly in children and adolescents. The disease is characterized by poor overall prognosis and lower survival due to a lack of predictive markers. Many gene signatures with diagnostic, prognostic, and predictive values were evaluated to achieve better clinical outcomes. Two public data series, GSE21257 and UCSC Xena, were used to identify the minimum number of robust genes needed for a predictive signature to guide prognosis of patients with osteosarcoma. The lasso regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Our in vitro experiments demonstrated that silencing MXI1 attenuated proliferation, migration, and invasion of osteosarcoma cells, confirming the important role of MXI1 in osteosarcoma progression. Thus, our study is novel and better suited than previously published prognostic protocols for osteosarcoma ( Wu Z.-l. et al, 2020 ; Qiu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our in vitro experiments demonstrated that silencing MXI1 attenuated proliferation, migration, and invasion of osteosarcoma cells, confirming the important role of MXI1 in osteosarcoma progression. Thus, our study is novel and better suited than previously published prognostic protocols for osteosarcoma ( Wu Z.-l. et al, 2020 ; Qiu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…Our in vitro experiments demonstrated that silencing MXI1 attenuated proliferation, migration, and invasion of osteosarcoma cells, confirming the important role of MXI1 in osteosarcoma progression. Thus, our study is novel and better suited than previously published prognostic protocols for osteosarcoma (Wu Z.-l. et al, 2020;Qiu et al, 2021). Cancer progression is highly correlated with the physiological state of osteosarcoma immune microenvironment that consists of innate as well as adaptive immune cells (Roma-Rodrigues et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study shows that STC2 is an outstanding immune-related gene during the progression of OS [ 33 ]. A recent study indicates that 20 genes including STC2 signatures are identified related to OS, which can be helpful for predicting prognosis of patients with OS [ 34 ]. SPARC1 protein can affect osteoblast differentiation, tumorigenesis and tumor metastasis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…With this treatment, the five-year survival rate of osteosarcoma patients with localized disease is 65–70%. Unfortunately, the patient develops resistance to neoadjuvant chemotherapy, resulting in metastasis and a five-year survival rate of 15–30% [ 1 , 4 ]. Based on the clinical outcome of osteosarcoma patients without overt metastatic sites at diagnosis, 90% of patients developed lung metastasis 6–36 months later, but metastases can also develop in bone (8–10%) and rarely in lymph nodes.…”
Section: Introductionmentioning
confidence: 99%